Arbitral Awards of the Cairo Regional Centre for International Commercial Arbitration - Arbitral Awards of CRCICA Volume 2 (1997-2000) - Alamedin, Mohiedin Ismail, (Brill Book Archive Part 1, ISBN: 9789004472495., 2003)
The cases are edited and translated by the prominent legal scholar, arbitrator and lawyer Dr. Mohie Eldin I. Alam-Eldin. His in-depth commentary on the thirty-four cases included in this volume encompasses discussion of emerging new arbitral trends and principles, such as the alter ego and contra preferentum doctrines, and new approaches to arbitration engendered by the ever-growing and changing practises and patterns of internatuional trade. He also analyses many of the new issues raised by the decisions of the court of appeal in cases where arbitral awards proved unsatisfactory. Many of these court of appeal decisions are included in the text, as are relevant decisions of the Supreme Court of Egypt. This second series of cases brought before the Cairo Regional Centre for International Commercial Arbitration covers the period 1997-2002, years which witnessed a major growth in confidence in the Centre and a corresponding expansion in scope, procedure, and legal principles. Perhaps most notable among these important developments is the evolution of hybrid procedures that permit the harmonization of legal cultures among parties. In this book will be found a number of cases which successfully blend common law, civil law, and Sharia principles while rigorously adhering to the agreements between the parties, all applicable law, and guarantees of defence. The subject matter of the international disputes arbitrated includes the following: - Supply - Hotel management - Software contracts - Oil contracts - Distributorship contracts - Insurance contracts - Credit risk management contracts - Construction - Commercial agency The significance of the Cairo Regional Centre for International Commercial Arbitration, as a forward-looking and innovative institution directly influencing business activity in some of the most important areas of global commerce, can hardly be overstated. This book validates and reinforces the Centre pivotal role, and will be of inestimable value to the international commercial arbitration community.